Index Risk of Sanitation (IRS) Modelling to Determine Domestic Waste Water System - Edy Santosa, Florianus Rooslan; Atmoko, Arief Dwi; Mudjanarko, Sri Wiwoho (International Journal of Sustainable Construction Engineering and Technology, 2020)
100% Clean water access and feasible sanitation are aims that mentioned within National Medium-Term Development Plan 2015-2019. The present study aims to create sanitation modelling to determine waste water management system and its sustainability. The present study shows two discriminant equations which are: 1) discriminant 1 : Z1 = -41.863 - (1.156*IRS) + (0,066*PM) + (0,160*PP) + (0,111*PWM), and discriminant 2 : Z2 = 6.743 + (1.542*IRS) + (0,014*PM) + (0,207*PP) - (0,256*PWM). Both discriminants are used to determine domestic waste water system; 2) Z1 = -4.011 + (1.246*PMS) + (3.699*KEU) + (1.164*KLM). This discriminant is used to determine the sustainability status in which a sub-district can be regarded as success (1) or failed (2). Variables that are used in determining waste water system are Index Risk Sanitation (IRS) Female Participation (PP), Poor People as Beneficiary (PWM), and Beneficiaries (PM). Meanwhile variables that influencing the sustainability status are Society Participation (PMS), Financial (KEU), and Regulation/Institutional (REG). First equation in form of Territorial Map and when it is applied into 154 sub-districts in Surabaya it shows result as follow: 1) Based on index risk sanitation: there are 9 sub-districts or 5,84% included as less risk area, 70 sub-districts or 45,451% included as medium risk area, 55 sub-districts or 35,71% included as high risk area, and 20 sub-districts or 12,99% included as very high risk area; 2) Based on Domestic Waste Water System: there are 57 sub-districts (37,01%) categorised in Domestic Communal System, 31 sub-districts (20,13%) categorised in Domestic IPAL Tube Sys-tem, and 66 sub-districts (42,86%) categorised in combination of communal and IPAL systems; and 3) Based on Sustain-ability Status of Domestic Waste Water System: there are 120 sub-districts (77,92%) regarded as success group dan 34 sub-districts (22,08%) regarded as failed group.